A foaming material formula and preparation method thereof

By using modified carbon nanotube composites as antistatic agents in foamed materials, the shortcomings of existing materials in antistatic properties and mechanical properties are solved, and high-performance foamed materials are achieved, meeting the needs of optoelectronic product packaging, and promoting the recycling of waste plastics.

CN119410042BActive Publication Date: 2025-04-15ANHUI YOURFRIEND PULP MOLDING TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510006723.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Existing foamed materials have shortcomings in antistatic, mechanical properties and dimensional stability, and it is difficult to meet the high-performance needs of optoelectronic product packaging.

Method used

Modified carbon nanotube composites are used as antistatic agents. By reacting with organic antistatic modifiers, their dispersion and compatibility in foamed materials are improved, thereby improving the antistatic and mechanical properties of the materials.

Benefits of technology

It significantly improves the antistatic and mechanical properties of foamed materials, including tensile strength, impact strength, etc., extends the service life of the material, and realizes the recycling and reuse of waste plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410042B_ABST
    Figure CN119410042B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of foaming materials, and in particular to a foaming material formula and a preparation method thereof. The foaming material formula is composed of the following parts by weight of raw materials: 20-50 parts by weight of waste plastic polyethylene / polystyrene copolymer, 50-100 parts by weight of nitrile rubber, 0.5-2 parts by weight of vulcanizing agent, 1-3 parts by weight of accelerator, 1-3 parts by weight of lubricant, 12-25 parts by weight of foaming agent, 2-5 parts by weight of nucleating agent, 1-3 parts by weight of cross-linking agent, 5-10 parts by weight of antistatic agent; the antistatic agent is a modified carbon nanotube or a modified carbon nanotube composite. The foaming material prepared by the present invention not only has excellent physical properties, but also has good antistatic effect, and mechanical properties are also improved. It meets the requirements of green environmental protection, so as to realize the recycling and reuse of waste plastics, and realize resource conservation and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a foaming material formula and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the optoelectronic industry has become an important pillar of the global high-tech industry, and its products are widely used in communications, medical, military, aerospace and other fields. However, the precision and fragility of optoelectronic products also put forward extremely high requirements on packaging materials. Packaging materials not only need to have excellent protective properties to ensure the safety of products during transportation and storage, but also need to comply with environmental protection trends. Plastic foam packaging materials are in great demand in industries such as machinery, electronics and electrical appliances, and biomedicine, accounting for about a quarter of the total global plastic consumption.

[0003] Polymer materials have the advantages of good comprehensive performance, recyclability, and low price, and are widely used. With the increasing requirements for environmental protection, the demand for multifunctional and environmentally friendly materials has increased significantly. Researchers have developed lightweight, efficient, and multifunctional polymer foam materials, which save costs, reduce environmental pollution, and achieve functional diversification. Polymer foam materials have a "sandwich" structure, and there are a large number of tiny bubbles in the core layer, so they are also called porous foam materials. They are widely used in automobiles, construction, protection, transportation, home appliances, packaging and other fields.

[0004] Polystyrene and rubber foam materials occupy an important position in the field of plastic packaging due to their unique combination of properties. Polyolefin regrind is increasingly widely used in the plastics industry. Recycling and reusing polyolefin regrind such as foamable polyethylene / polystyrene copolymer (EPO) is an inevitable trend to achieve low-carbon development of plastic foam packaging materials. In order to realize the industrialization of high-performance recyclable foamed polystyrene / rubber copolymer (ERPO) foam materials, the present invention starts from the aspects of material formulation, molding process and product performance, and focuses on breaking through the key manufacturing technology of high-performance ERPO foam materials, so that it can be used for optoelectronic product packaging, and through material modification, formula design and foaming process optimization, the antistatic property, dimensional stability and mechanical properties of ERPO foam materials are significantly improved, so that it can meet the packaging needs of optoelectronic products, meet customers' customized requirements for product functionality, realize product value-added, and improve economic benefits. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a foaming material formula and a preparation method thereof.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0007] A foaming material formula is composed of the following raw materials in parts by weight: 20-50 parts by weight of waste plastic polyethylene / polystyrene copolymer, 50-100 parts by weight of nitrile rubber, 0.5-2 parts by weight of vulcanizing agent, 1-3 parts by weight of accelerator, 1-3 parts by weight of lubricant, 12-25 parts by weight of foaming agent, 2-5 parts by weight of nucleating agent, 1-3 parts by weight of crosslinking agent, and 5-10 parts by weight of antistatic agent; the antistatic agent is modified carbon nanotube or modified carbon nanotube composite.

[0008] The vulcanizing agent is at least one of benzoyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, and 2,4-dichlorobenzoyl peroxide.

[0009] The promoter is any one of cyclopentane, monofluorodichloroethane and ionic liquid.

[0010] The lubricant is any one of polyethylene wax, zinc stearate, glyceryl monostearate and stearic acid.

[0011] The foaming agent is any one of toluenesulfonyl hydrazide, azodicarbonamide and azobisisobutyronitrile.

[0012] The nucleating agent is any one of rectorite, talc, montmorillonite and silicon dioxide.

[0013] The cross-linking agent is any one of di-tert-butyl diisopropylbenzene peroxide, diisopropylbenzene peroxide and divinylbenzene.

[0014] The present invention uses recycled plastics such as polyethylene / polystyrene copolymers as raw materials for foaming materials, which achieves low cost, resource utilization of waste plastics, reduces environmental pollution, and increases the second advantage of the project's environmental benefits. However, the antistatic, impact resistance and water barrier properties of the foaming material prepared using this material still need to be improved to meet the customer's customized requirements for product functionality, achieve product value-added, and improve economic benefits. In order to solve the static electricity problem of the foaming material, carbon nanotubes, carbon black, graphite, metal-based conductive fillers or traditional small molecule antistatic agents are usually added to achieve the corresponding antistatic purpose, but there are usually problems such as uneven distribution of fillers, poor compatibility, easy precipitation, and deterioration of color, and the antistatic effect is short-lived, which affects the use of the material. Therefore, in order to improve the function of the foaming material, the present invention optimizes and modifies the carbon nanotubes.

[0015] The surface of the organic antistatic modifier prepared by the present invention contains hydroxyl groups, which may improve the conductivity of the polymer system, make static electricity more easily conducted to the outside of the system, reduce the accumulation of static electricity or give the material surface better lubricity, reduce the friction coefficient, and inhibit and reduce the generation of static charge; on the other hand, the hydroxyl groups on these structural chains can also play a role in "neutralizing" the charge; by adding the antistatic agent to react with the carboxyl group of the carboxylated carbon nanotubes, the compatibility of the antistatic agent with the substrate and the dispersibility in the material can be improved, thereby achieving a long-term antistatic effect, having better mechanical properties, and extending the service life.

[0016] Since the surface of carboxylated carbon nanotubes has been modified and has abundant -COOH groups, they can undergo condensation reaction with organic antistatic modifiers containing hydroxyl groups on the surface, and then have good compatibility with the polymer matrix polyethylene / polystyrene copolymer and nitrile rubber in the foaming material, thereby improving the dispersion of the modified carbon nanotube composite in the polymer matrix of the foaming material, thereby greatly improving the antistatic performance of the foaming material. The high dispersion of the modified carbon nanotube composite in the foaming material improves the defect of easy agglomeration of the antistatic component, and greatly improves the tensile strength, elongation at break, impact strength and other mechanical properties of the foaming material.

[0017] The specific reaction mechanism is as follows: S1 uses 4-vinylbenzyl glycidyl ether as a reaction monomer, potassium tert-butoxide as an initiator, and tetrahydrofuran as a reaction solvent. The vinyl group is deprotonated by potassium tert-butoxide to form an active anion intermediate, and poly 4-vinylbenzyl glycidyl ether is prepared by anionic ring-opening polymerization under heating conditions. Finally, the reaction is terminated by hydrochloric acid to obtain a poly 4-vinylbenzyl glycidyl ether intermediate; S2 uses an intermediate product containing vinyl groups and nano-cadmium sulfide as a catalyst. Under blue light irradiation, nano-cadmium sulfide can excite electrons and promote the reaction of thiol and vinyl groups, which can react with nonanethiol through The thiol-ene click chemistry reaction forms a sulfide bond, which enhances the reaction rate and efficiency and obtains an organic antistatic modifier. S3 uses carboxylated carbon nanotubes as reaction raw materials and N,N-dimethylformamide as a reaction solvent for mixing and dispersing under ultrasonic conditions to improve the dispersibility of the carbon nanotubes and increase their contact area with the organic antistatic modifier. The organic antistatic modifier is added to the dispersion of the carbon nanotubes, and the reaction of the modifier with the carboxyl group on the surface of the carbon nanotubes is promoted by ultrasound and stirring to form an amide bond or an ester bond, thereby fixing the modifier on the surface of the carbon nanotubes to obtain a modified carbon nanotube composite.

[0018] The modified carbon nanotubes used in the present invention have excellent electrical conductivity. When added to the foaming material as an antistatic agent, an electron transmission path from the surface of the foaming material to the ground can be provided, and the static charge accumulated on the surface can be quickly neutralized, and the risk of electrostatic discharge can be reduced, and the electrical conductivity of the material can be significantly improved, thereby effectively preventing static electricity accumulation; carbon nanotubes have extremely high strength and modulus, which can not only improve the dimensional stability of the material, but also their dispersion in the foaming material can enhance the mechanical properties of the material, such as tensile strength, compression strength, impact resistance and tear resistance. The added modifier is a conductive polymer, and the method for improving the conductivity of the polymer is to add a filler with high conductivity, also known as an antistatic agent, and its mechanism of action is to reduce the material's obstacles to electrons, improve the conductive effect of the material, enable the charge to be transferred on the surface and inside, improve the friction performance of the material surface, and avoid the generation of charge and accumulation. The antistatic properties of the polymer are usually improved by adding an antistatic agent. The two synergistically enhance the antistatic effect of the foaming material and improve the mechanical properties of the foaming material at the same time.

[0019] The preparation method of the modified carbon nanotube composite is as follows:

[0020] S1: 4-8 parts by weight of 4-vinylbenzyl glycidyl ether, 0.2-0.8 parts by weight of potassium tert-butoxide and 60-120 parts by weight of tetrahydrofuran are uniformly mixed, and polymerized at 60-80° C. for 12-28 hours, and 0.5-2 mol / L hydrochloric acid is added to terminate the polymerization reaction, and the solvent is distilled off under reduced pressure to obtain an intermediate product;

[0021] S2: 2-5 parts by weight of the above intermediate product, 3-8 parts by weight of nonanethiol, 0.05-0.2 parts by weight of nano-cadmium sulfide and 40-100 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 1-3 hours at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier;

[0022] S3: 3-8 parts by weight of carboxylated carbon nanotubes and 60-120 parts by weight of N,N-dimethylformamide are mixed, ultrasonically dispersed at an ultrasonic power of 100-300 W and an ultrasonic frequency of 40-70 kHz for 1-4 hours, and then 1-5 parts by weight of the above-mentioned organic antistatic modifier are added and ultrasonicated for 0.5-2 hours. Finally, the mixture is stirred at 55-70° C. and 400-800 rpm for 4-10 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

[0023] The method for preparing the foaming material formula comprises the following steps:

[0024] (1) Placing the waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 200-400 rpm and 170-190° C. for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 6000-10000 rpm, placing in a twin-screw extruder at 200-400 rpm and 170-190° C. for blending and granulation to obtain blended granules;

[0025] (2) using the blended particles prepared above as a resin matrix, mixing them with a promoter, an antistatic agent, and a nucleating agent respectively, and again passing through a twin-screw extruder to prepare the desired mixed particles;

[0026] (3) placing the blended material particles into an injection molding machine, and performing injection molding at 170-190° C. and 10-15 MPa to obtain a rectangular parallelepiped material to be foamed;

[0027] (4) The material to be foamed is placed in a supercritical foaming reactor at 130-140°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 2-5MPa, and then nitrogen is introduced to a total pressure of 18-22MPa. The temperature and pressure are maintained for 1-3 hours, and the pressure is quickly released to obtain a foamed material.

[0028] The twin screw zones 1 to 10 in the step (2) are 110-140°C, 170-190°C, 170-190°C, 170-190°C, 170-190°C, 170-190°C, 160-180°C, 160-180°C, 160-180°C, and 150-170°C respectively, the die temperature is 140-150°C, the screw aspect ratio of the twin screw extruder is 32-38:1, and the screw speed is 300-500rpm.

[0029] Beneficial effects of the invention: The invention provides a foaming material formula and a preparation method thereof, and the prepared foaming material not only has excellent physical properties, but also has good antistatic effect and water barrier effect, and the mechanical properties are also improved. It also meets the requirements of green environmental protection, so as to realize the recycling and reuse of waste plastics, and realize resource conservation and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the foamed material prepared in Example 1.

[0031] Figure 2 This is the SEM image of the foamed material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0032] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.

[0033] Introduction of some raw materials in this application:

[0034] Waste plastic polyethylene / polystyrene copolymer was provided by Nanjing Suhong Recycling Resources Co., Ltd.

[0035] The nitrile rubber was purchased from Jining Fangyu Chemical Co., Ltd., model TL55.

[0036] Carboxylated carbon nanotubes were purchased from Shanghai Ziyi Reagent Factory, catalog number: 131110.

[0037] Example 1

[0038] A foaming material formula is composed of the following raw materials in parts by weight: 30 parts by weight of waste plastic polyethylene / polystyrene copolymer, 80 parts by weight of nitrile rubber, 1 part by weight of vulcanizing agent, 2 parts by weight of accelerator, 2 parts by weight of lubricant, 18 parts by weight of foaming agent, 3 parts by weight of nucleating agent, 2 parts by weight of crosslinking agent, and 8 parts by weight of antistatic agent.

[0039] The vulcanizing agent is benzoyl peroxide.

[0040] The promoter is cyclopentane.

[0041] The lubricant is zinc stearate.

[0042] The foaming agent is azodicarbonamide.

[0043] The nucleating agent is rectorite.

[0044] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0045] The antistatic agent is a modified carbon nanotube composite, and the preparation method of the modified carbon nanotube composite is as follows:

[0046] S1: 6 parts by weight of 4-vinylbenzyl glycidyl ether, 0.5 parts by weight of potassium tert-butoxide and 80 parts by weight of tetrahydrofuran were uniformly mixed, and polymerized at 70° C. for 18 h, 1 mol / L hydrochloric acid was added to terminate the polymerization reaction, and the solvent was distilled off under reduced pressure to obtain an intermediate product;

[0047] S2: 3 parts by weight of the above intermediate product, 5 parts by weight of nonanethiol, 0.1 parts by weight of nano-cadmium sulfide and 50 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 1.5 hours at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier;

[0048] S3: 5 parts by weight of carboxylated carbon nanotubes and 80 parts by weight of N,N-dimethylformamide are mixed, ultrasonically dispersed at an ultrasonic power of 200 W and an ultrasonic frequency of 60 kHz for 2 hours, and then 3 parts by weight of the above-mentioned organic antistatic modifier are added and ultrasonicated for 1 hour. Finally, the mixture is stirred at 60°C and 600 rpm for 6 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

[0049] A method for preparing a foaming material formula comprises the following steps:

[0050] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 300 rpm and 180°C for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 8000 rpm, placing in a twin-screw extruder at 300 rpm and 180°C for blending granulation to obtain blended granules;

[0051] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the temperatures of zones 1 to 10 are 120° C., 180° C., 180° C., 180° C., 180° C., 180° C., 170° C., 170° C., 170° C., 160° C., respectively, the die temperature is 145° C., the screw aspect ratio of the twin-screw extruder is 35:1, and the screw speed is 400 rpm;

[0052] (3) placing the blended material particles into an injection molding machine and performing injection molding at 180°C and 12 MPa to obtain a rectangular parallelepiped material to be foamed;

[0053] (4) The material to be foamed is placed in a supercritical foaming reactor at 135°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 3 MPa, and then nitrogen is introduced to a total pressure of 20 MPa. The temperature and pressure are maintained for 2 hours, and the pressure is quickly released to obtain a foamed material.

[0054] Example 2

[0055] A foaming material formula is composed of the following raw materials in parts by weight: 20 parts by weight of waste plastic polyethylene / polystyrene copolymer, 50 parts by weight of nitrile rubber, 0.5 parts by weight of vulcanizing agent, 1 part by weight of accelerator, 1 part by weight of lubricant, 12 parts by weight of foaming agent, 2 parts by weight of nucleating agent, 1 part by weight of cross-linking agent, and 5 parts by weight of antistatic agent.

[0056] The vulcanizing agent is benzoyl peroxide.

[0057] The promoter is cyclopentane.

[0058] The lubricant is zinc stearate.

[0059] The foaming agent is azodicarbonamide.

[0060] The nucleating agent is rectorite.

[0061] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0062] The antistatic agent is a modified carbon nanotube composite, and the preparation method of the modified carbon nanotube composite is as follows:

[0063] S1: 4 parts by weight of 4-vinylbenzyl glycidyl ether, 0.2 parts by weight of potassium tert-butoxide and 60 parts by weight of tetrahydrofuran were uniformly mixed, and polymerized at 60° C. for 12 h, and 0.5 mol / L hydrochloric acid was added to terminate the polymerization reaction, and the solvent was distilled off under reduced pressure to obtain an intermediate product;

[0064] S2: 2 parts by weight of the above intermediate product, 3 parts by weight of nonanethiol, 0.05 parts by weight of nano-cadmium sulfide and 40 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 1 hour at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier;

[0065] S3: 3 parts by weight of carboxylated carbon nanotubes and 60 parts by weight of N,N-dimethylformamide are mixed, and ultrasonic dispersion is performed at an ultrasonic power of 100 W and an ultrasonic frequency of 40 kHz for 1 hour. Then, 1 part by weight of the above-mentioned organic antistatic modifier is added and ultrasonic dispersion is continued for 0.5 hours. Finally, the mixture is stirred at 55°C and 400 rpm for 4 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

[0066] A method for preparing a foaming material formula comprises the following steps:

[0067] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 200 rpm and 170°C for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 6000 rpm, placing in a twin-screw extruder at 200 rpm and 170°C for blending granulation to obtain blended granules;

[0068] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the temperatures of zones 1 to 10 are 110° C., 170° C., 170° C., 170° C., 170° C., 170° C., 160° C., 160° C., 150° C., the die temperature is 140° C., the screw aspect ratio of the twin-screw extruder is 32:1, and the screw speed is 300 rpm;

[0069] (3) placing the blended material particles into an injection molding machine and performing injection molding at 170° C. and 10 MPa to obtain a rectangular parallelepiped material to be foamed;

[0070] (4) The material to be foamed is placed in a supercritical foaming reactor at 130°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 2 MPa, and then nitrogen is introduced to a total pressure of 18 MPa. The temperature and pressure are maintained for 1 hour, and the pressure is quickly released to obtain a foamed material.

[0071] Example 3

[0072] A foaming material formula is composed of the following raw materials in parts by weight: 50 parts by weight of waste plastic polyethylene / polystyrene copolymer, 100 parts by weight of nitrile rubber, 2 parts by weight of vulcanizing agent, 3 parts by weight of accelerator, 3 parts by weight of lubricant, 25 parts by weight of foaming agent, 5 parts by weight of nucleating agent, 3 parts by weight of crosslinking agent, and 10 parts by weight of antistatic agent.

[0073] The vulcanizing agent is benzoyl peroxide.

[0074] The promoter is cyclopentane.

[0075] The lubricant is zinc stearate.

[0076] The foaming agent is azodicarbonamide.

[0077] The nucleating agent is rectorite.

[0078] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0079] The antistatic agent is a modified carbon nanotube composite, and the preparation method of the modified carbon nanotube composite is as follows:

[0080] S1 8 parts by weight of 4-vinylbenzyl glycidyl ether, 0.8 parts by weight of potassium tert-butoxide and 120 parts by weight of tetrahydrofuran were uniformly mixed, and polymerized at 80° C. for 28 hours, and 2 mol / L hydrochloric acid was added to terminate the polymerization reaction, and the solvent was distilled off under reduced pressure to obtain an intermediate product;

[0081] S2: 5 parts by weight of the above intermediate product, 8 parts by weight of nonanethiol, 0.2 parts by weight of nano-cadmium sulfide and 100 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 3 hours at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier;

[0082] S3: 8 parts by weight of carboxylated carbon nanotubes and 120 parts by weight of N,N-dimethylformamide are mixed, ultrasonically dispersed at an ultrasonic power of 300 W and an ultrasonic frequency of 70 kHz for 4 hours, and then 5 parts by weight of the above-mentioned organic antistatic modifier are added and ultrasonicated for 2 hours. Finally, the mixture is stirred at 70°C and 800 rpm for 10 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

[0083] A method for preparing a foaming material formula comprises the following steps:

[0084] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 400 rpm and 190° C. for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 10,000 rpm, and placing in a twin-screw extruder at 400 rpm and 190° C. for blending granulation to obtain blended granules;

[0085] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the 1 to 10 zones are 140° C., 190° C., 190° C., 190° C., 190° C., 190° C., 180° C., 180° C., 170° C., the die temperature is 150° C., the screw aspect ratio of the twin-screw extruder is 38:1, and the screw speed is 500 rpm;

[0086] (3) placing the blended material particles into an injection molding machine and performing injection molding at 190°C and 15 MPa to obtain a rectangular parallelepiped material to be foamed;

[0087] (4) The material to be foamed is placed in a supercritical foaming reactor at 140°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 5 MPa, and then nitrogen is introduced to a total pressure of 22 MPa. The temperature and pressure are maintained for 3 hours, and the pressure is quickly released to obtain a foamed material.

[0088] Comparative Example 1

[0089] A foaming material formula is composed of the following raw materials in parts by weight: 30 parts by weight of waste plastic polyethylene / polystyrene copolymer, 80 parts by weight of nitrile rubber, 1 part by weight of vulcanizing agent, 2 parts by weight of accelerator, 2 parts by weight of lubricant, 18 parts by weight of foaming agent, 3 parts by weight of nucleating agent, 2 parts by weight of crosslinking agent, and 8 parts by weight of antistatic agent.

[0090] The vulcanizing agent is benzoyl peroxide.

[0091] The promoter is cyclopentane.

[0092] The lubricant is zinc stearate.

[0093] The foaming agent is azodicarbonamide.

[0094] The nucleating agent is rectorite.

[0095] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0096] The antistatic agent is carboxylated carbon nanotubes.

[0097] A method for preparing a foaming material formula comprises the following steps:

[0098] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 300 rpm and 180°C for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 8000 rpm, placing in a twin-screw extruder at 300 rpm and 180°C for blending granulation to obtain blended granules;

[0099] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the temperatures of zones 1 to 10 are 120° C., 180° C., 180° C., 180° C., 180° C., 180° C., 170° C., 170° C., 170° C., 160° C., respectively, the die temperature is 145° C., the screw aspect ratio of the twin-screw extruder is 35:1, and the screw speed is 400 rpm;

[0100] (3) placing the blended material particles into an injection molding machine and performing injection molding at 180°C and 12 MPa to obtain a rectangular parallelepiped material to be foamed;

[0101] (4) The material to be foamed is placed in a supercritical foaming reactor at 135°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 3 MPa, and then nitrogen is introduced to a total pressure of 20 MPa. The temperature and pressure are maintained for 2 hours, and the pressure is quickly released to obtain a foamed material.

[0102] Comparative Example 2

[0103] A foaming material formula is composed of the following raw materials in parts by weight: 30 parts by weight of waste plastic polyethylene / polystyrene copolymer, 80 parts by weight of nitrile rubber, 1 part by weight of vulcanizing agent, 2 parts by weight of accelerator, 2 parts by weight of lubricant, 18 parts by weight of foaming agent, 3 parts by weight of nucleating agent, 2 parts by weight of crosslinking agent, and 8 parts by weight of antistatic agent.

[0104] The vulcanizing agent is benzoyl peroxide.

[0105] The promoter is cyclopentane.

[0106] The lubricant is zinc stearate.

[0107] The foaming agent is azodicarbonamide.

[0108] The nucleating agent is rectorite.

[0109] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0110] The antistatic agent is a modified carbon nanotube composite, and the preparation method of the modified carbon nanotube composite is as follows:

[0111] S1: 6 parts by weight of 4-vinylbenzyl glycidyl ether, 0.5 parts by weight of potassium tert-butoxide and 80 parts by weight of tetrahydrofuran were uniformly mixed, and polymerized at 70° C. for 18 h, 1 mol / L hydrochloric acid was added to terminate the polymerization reaction, and the solvent was distilled off under reduced pressure to obtain an intermediate product;

[0112] S2: 3 parts by weight of the above intermediate product, 5 parts by weight of nonanethiol, 0.1 parts by weight of nano-cadmium sulfide and 50 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 1.5 hours at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier;

[0113] S3: 5 parts by weight of carbon nanotubes and 80 parts by weight of N,N-dimethylformamide are mixed, ultrasonically dispersed at an ultrasonic power of 200 W and an ultrasonic frequency of 60 kHz for 2 hours, and then 3 parts by weight of the above-mentioned organic antistatic modifier are added and ultrasonication is continued for 1 hour. Finally, the mixture is stirred at 60°C and 600 rpm for 6 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

[0114] A method for preparing a foaming material formula comprises the following steps:

[0115] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 300 rpm and 180°C for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 8000 rpm, placing in a twin-screw extruder at 300 rpm and 180°C for blending granulation to obtain blended granules;

[0116] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the temperatures of zones 1 to 10 are 120° C., 180° C., 180° C., 180° C., 180° C., 180° C., 170° C., 170° C., 170° C., 160° C., respectively, the die temperature is 145° C., the screw aspect ratio of the twin-screw extruder is 35:1, and the screw speed is 400 rpm;

[0117] (3) placing the blended material particles into an injection molding machine and performing injection molding at 180°C and 12 MPa to obtain a rectangular parallelepiped material to be foamed;

[0118] (4) The material to be foamed is placed in a supercritical foaming reactor at 135°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 3 MPa, and then nitrogen is introduced to a total pressure of 20 MPa. The temperature and pressure are maintained for 2 hours, and the pressure is quickly released to obtain a foamed material.

[0119] Comparative Example 3

[0120] A foaming material formula is composed of the following raw materials in parts by weight: 30 parts by weight of waste plastic polyethylene / polystyrene copolymer, 80 parts by weight of nitrile rubber, 1 part by weight of vulcanizing agent, 2 parts by weight of accelerator, 2 parts by weight of lubricant, 18 parts by weight of foaming agent, 3 parts by weight of nucleating agent, 2 parts by weight of crosslinking agent, and 8 parts by weight of antistatic agent.

[0121] The vulcanizing agent is benzoyl peroxide.

[0122] The promoter is cyclopentane.

[0123] The lubricant is zinc stearate.

[0124] The foaming agent is azodicarbonamide.

[0125] The nucleating agent is rectorite.

[0126] The cross-linking agent is di-tert-butyl diisopropylbenzene peroxide.

[0127] The preparation method of the antistatic agent is as follows:

[0128] S1: 6 parts by weight of 4-vinylbenzyl glycidyl ether, 0.5 parts by weight of potassium tert-butoxide and 80 parts by weight of tetrahydrofuran were uniformly mixed, and polymerized at 70° C. for 18 h, 1 mol / L hydrochloric acid was added to terminate the polymerization reaction, and the solvent was distilled off under reduced pressure to obtain an intermediate product;

[0129] S2: 3 parts by weight of the above intermediate product, 5 parts by weight of nonanethiol, 0.1 parts by weight of nano-cadmium sulfide and 50 parts by weight of N,N-dimethylformamide are mixed, and irradiated under blue light for 1.5 hours at room temperature. After the reaction is completed, the mixture is filtered and the mixed solution obtained after filtration is distilled under reduced pressure to obtain an antistatic agent.

[0130] A method for preparing a foaming material formula comprises the following steps:

[0131] (1) Placing waste plastic polyethylene / polystyrene copolymer in a twin-screw extruder at a speed of 300 rpm and 180°C for melting, extrusion granulation, and drying to obtain granules; then mixing the granules, nitrile rubber, vulcanizing agent, lubricant, and cross-linking agent in a high-speed mixer at 8000 rpm, placing in a twin-screw extruder at 300 rpm and 180°C for blending granulation to obtain blended granules;

[0132] (2) The prepared blended particles are used as a resin matrix, mixed with a promoter, an antistatic agent, and a nucleating agent respectively, and then passed through a twin-screw extruder again to prepare the desired mixed particles; the temperatures of zones 1 to 10 are 120° C., 180° C., 180° C., 180° C., 180° C., 180° C., 170° C., 170° C., 170° C., 160° C., respectively, the die temperature is 145° C., the screw aspect ratio of the twin-screw extruder is 35:1, and the screw speed is 400 rpm;

[0133] (3) placing the blended material particles into an injection molding machine and performing injection molding at 180°C and 12 MPa to obtain a rectangular parallelepiped material to be foamed;

[0134] (4) The material to be foamed is placed in a supercritical foaming reactor at 135°C, carbon dioxide is first introduced to pressurize the supercritical foaming reactor to 3 MPa, and then nitrogen is introduced to a total pressure of 20 MPa. The temperature and pressure are maintained for 2 hours, and the pressure is quickly released to obtain a foamed material.

[0135] Test Example 1

[0136] Antistatic performance test: The test was carried out using the method in the national standard GB / T15662-1995 "Test method for volume resistivity of conductive and antistatic plastics". The foamed materials prepared in the above embodiments and comparative examples were injection molded by an injection molding machine. The sample length was 100 mm, the width was 10 mm, and the thickness was 4 mm. The test conditions were: relative temperature: 23°C, relative humidity: 50%. Six groups were tested in parallel and the average value was taken. The results are shown in Table 1.

[0137] Table 1. Antistatic test results of foaming materials

[0138] Resistivity (Ω·m) Example 1 <![CDATA[3.5×10 5 ]]> Example 2 <![CDATA[8.9×10 5 ]]> Example 3 <![CDATA[1.1×10 6 ]]> Comparative Example 1 <![CDATA[7.3×10 8 ]]> Comparative Example 2 <![CDATA[8.4×10 7 ]]> Comparative Example 3 <![CDATA[3.5×10 8 ]]>

[0139] Test Example 2

[0140] 1. Tensile property test: The test was conducted using the national standard GB / T1040.3-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics" method; the foamed materials prepared in the above embodiments and comparative examples were injection molded by an injection molding machine, the test specimen was a 1A dumbbell type with a thickness of 4 mm, the test speed was 1 mm / min, 5 groups were paralleled, and the average value was taken. The results are shown in Table 2.

[0141] 2. Impact performance test: The national standard GB / T1843-2008 "Test of cantilever beam impact strength" was used for testing, with a thickness of 4 mm, 5 parallel groups, and the average value was taken. The results are shown in Table 2.

[0142] Table 2. Mechanical properties test of antistatic materials of foaming materials

[0143] Tensile strength (MPa) <![CDATA[Notched impact strength (kJ / m 2 ).]]> Example 1 10.9 37.2 Example 2 10.1 35.9 Example 3 9.4 35.1 Comparative Example 1 6.9 28.9 Comparative Example 2 8.3 32.1 Comparative Example 3 6.1 26.1

[0144] From the above results, it can be seen that the foamed material prepared by the present invention has good antistatic effect and also has good mechanical properties. Figure 1 and Figure 2 It can be clearly seen that after the modified process of the modified carbon nanotube composite is used, the recycled material, rubber and polystyrene are distributed in a honeycomb pattern, and the arrangement is more neat, thereby greatly improving the impact strength and toughness. Specifically comparing Example 1 with Comparative Example 1 and Comparative Example 3, it can be known that the modified carbon nanotubes used in the present invention have excellent electrical conductivity. Adding them as antistatic agents to the foaming material can provide an electron transmission path from the surface of the foaming material to the ground, quickly neutralize the static charge accumulated on the surface, reduce the risk of electrostatic discharge, and significantly improve the electrical conductivity of the material, thereby effectively preventing static electricity accumulation; carbon nanotubes have extremely high strength and modulus, which can not only improve the dimensional stability of the material, but also their dispersion in the foaming material can enhance the mechanical properties of the material, such as tensile strength, compression strength, impact resistance and tear resistance. The added modifier is a conductive polymer. The method for improving the conductivity of the polymer is to add a filler with high conductivity, also known as an antistatic agent. Its mechanism of action is to reduce the material's obstacles to electrons, improve the conductive effect of the material, enable the charge to be transferred on the surface and inside, improve the friction performance of the material surface, and avoid the generation of charge and accumulation. The antistatic properties of polymers are usually improved by adding antistatic agents. The two synergistically enhance the antistatic effect of the foamed material and improve the mechanical properties of the foamed material.

[0145] Since the surface of carboxylated carbon nanotubes has been modified and has abundant -COOH groups, they can undergo condensation reaction with organic antistatic modifiers containing hydroxyl groups on the surface, and then have good compatibility with the polymer matrix polyethylene / polystyrene copolymer and nitrile rubber in the foaming material, thereby improving the dispersion of the modified carbon nanotube composite in the polymer matrix of the foaming material, thereby greatly improving the antistatic performance of the foaming material. The high dispersion of the modified carbon nanotube composite in the foaming material improves the defect of easy agglomeration of the antistatic component, and greatly improves the tensile strength, elongation at break, impact strength and other mechanical properties of the foaming material.

[0146] The surface of the organic antistatic modifier prepared by the present invention contains hydroxyl groups, which may improve the conductivity of the polymer system, make static electricity more easily conducted to the outside of the system, reduce the accumulation of static electricity or give the material surface better lubricity, reduce the friction coefficient, and inhibit and reduce the generation of static charge; on the other hand, the hydroxyl groups on these structural chains can also play a role in "neutralizing" the charge; by adding the antistatic agent to react with the carboxyl group of the carboxylated carbon nanotubes, the compatibility of the antistatic agent with the substrate and the dispersibility in the material can be improved, thereby achieving a long-term antistatic effect, having better mechanical properties, and extending the service life.

Claims

1. A foaming material, characterized in that: The invention is composed of the following raw materials in parts by weight: 20-50 parts by weight of waste plastic polyethylene / polystyrene copolymer, 50-100 parts by weight of nitrile rubber, 0.5-2 parts by weight of vulcanizing agent, 1-3 parts by weight of accelerator, 1-3 parts by weight of lubricant, 12-25 parts by weight of foaming agent, 2-5 parts by weight of nucleating agent, 1-3 parts by weight of crosslinking agent, and 5-10 parts by weight of antistatic agent; the antistatic agent is a modified carbon nanotube composite; and the preparation method of the modified carbon nanotube composite is as follows: S1: 4-8 parts by weight of 4-vinylbenzyl glycidyl ether, 0.2-0.8 parts by weight of potassium tert-butoxide and 60-120 parts by weight of tetrahydrofuran are uniformly mixed, and the mixture is polymerized at 60-80° C. for 12-28 hours, and 0.5-2 mol / L hydrochloric acid is added to terminate the polymerization reaction, and the solvent is removed by distillation under reduced pressure to obtain an intermediate product; S2: 2-5 parts by weight of the above intermediate product, 3-8 parts by weight of nonanethiol, 0.05-0.2 parts by weight of nano-cadmium sulfide and 40-100 parts by weight of N,N-dimethylformamide are mixed, irradiated under blue light for 1-3 hours at room temperature, filtered after the reaction is completed, and the mixed solution obtained after filtration is subjected to reduced pressure distillation to obtain an organic antistatic modifier; S3: 3-8 parts by weight of carboxylated carbon nanotubes and 60-120 parts by weight of N,N-dimethylformamide are mixed, ultrasonically dispersed at an ultrasonic power of 100-300 W and an ultrasonic frequency of 40-70 kHz for 1-4 hours, and then 1-5 parts by weight of the above-mentioned organic antistatic modifier are added and ultrasonicated for 0.5-2 hours. Finally, the mixture is stirred at 55-70° C. and 400-800 rpm for 4-10 hours, filtered, washed, and dried to obtain a modified carbon nanotube composite.

2. The foam material according to claim 1, characterized in that The vulcanizing agent is at least one of benzoyl peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, and 2,4-dichlorobenzoyl peroxide.

3. The foam material according to claim 1, characterized in that The promoter is any one of cyclopentane, monofluorodichloroethane and ionic liquid.

4. The foam material according to claim 1, characterized in that The lubricant is any one of polyethylene wax, zinc stearate, glyceryl monostearate and stearic acid.

5. The foam material according to claim 1, characterized in that: The foaming agent is any one of toluenesulfonyl hydrazide, azodicarbonamide and azobisisobutyronitrile.

6. The foam material according to claim 1, characterized in that: The nucleating agent is any one of rectorite, talc, montmorillonite and silicon dioxide.

7. The foam material according to claim 1, characterized in that: The crosslinking agent is any one of di-tert-butyl diisopropylbenzene peroxide, diisopropylbenzene peroxide and divinylbenzene.

Citation Information

Patent Citations

  • Antistatic anti-slip rubber-plastic foamed shoe sole and preparation method thereof

    CN104356496A

  • Antistatic antibacterial engineering plastic and preparation method thereof

    CN116751420A

  • Regenerated polyethylene foam material and preparation method thereof

    CN116814013A